A Single Fasting Exhaled Methane Level Correlates With Fecal Methanogen Load, Clinical Symptoms and Accurately Detects Intestinal Methanogen Overgrowth. (17th March 2022) - Takakura, Will; Pimentel, Mark; Rao, Satish; Villanueva-Millan, Maria Jesus; Chang, Christine; Morales, Walter; Sanchez, Maritza; Torosyan, John; Rashid, Mohamad; Hosseini, Ava; Wang, Jiajing; Leite, Gabriela; et al.
Abstract : INTRODUCTION: A 2-hour breath test is the gold standard for diagnosing intestinal methanogen overgrowth (IMO). This method can be cumbersome especially if used repetitively to monitor treatment response. Therefore, we aimed to assess the reliability of a fasting single methane measurement (SMM) in diagnosing IMO and its utility as a biomarker to monitor treatment response in subjects with IMO. METHODS: First, we calculated the test characteristics of SMM compared with lactulose and glucose breath test in 2 large-scale retrospective cohorts. Second, the symptomology associated with SMM using various cutoffs was analyzed. Third, in a double-blind randomized control trial, the temporal stability of SMM levels in subjects taking placebo was analyzed. Fourth, stool Methanobrevibacter smithii loads were quantified using quantitative polymerase chain reaction and compared with SMM levels. Last, the change in SMM over time during antibiotic therapy was analyzed. RESULTS: Using the cutoff of SMM ≥10 ppm, SMM had a sensitivity of 86.4% and specificity of 100% for diagnosing IMO on the glucose and lactulose breath tests and was associated with constipation (5.65 ± 3.47 vs 4.32 ± 3.62, P = 0.008). SMM remained stable for 14 weeks without treatment ( P = 0.45), and antibiotics lead to a decrease in SMM after 2 days ( P < 0.0001). SMM was positively associate with stool M. smithii load (R = 0.65, P < 0.0001). DISCUSSION: Fasting SMM ≥10 ppm seems to accurately diagnose IMO, is associated with constipation, and correlates with stool M. smithii . SMM seems to be stable without treatment and decreases after antibiotics. SMM may be a useful test to diagnose IMO and monitor treatment response.